Energy scavenging-aided NOMA uplink communications: performance analysis - Huu Q. Tran; Khuong Ho-Van (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
Energy scavenging-aided nonorthogonal multiple access (NOMA) networks significantly ameliorate energy-and-spectral efficiencies thanks to superimposing a multitude of user signals for concurrent transmission and harvesting radio frequency energy. Practically, energy harvesters possess non-linear characteristic and their efficiency is enhanced considerably with deployment of multiple antennas. Moreover, communication reliability and harvested energy are directly influenced by wireless propagation which induces simultaneous effects of shadowing, path loss, and fading. Accordingly, the current paper assesses analytically outage probability and throughput of energy scavenging (ES)-aided NOMA uplink communications (eNOMAu) taking into account the above-addressed realistic factors (κ − µ shadowed fading, multi-antenna deployment, ES nonlinearity). The results reveal considerable performance degradation caused by ES non-linearity and wireless propagation. Additionally, desired system performance can be reached flexibly with appropriate specification selection. In addition, accreting a quantity of antennas drastically mitigates the outage probability of eNOMAu, which can be minimized with optimal ES time selection. Furthermore, the proposed eNOMAu is considerably superior to its eOMAu counterpart.